Peran Guru Aqidah Akhlak dalam Meningkatkan Ketaatan Siswa terhadap Peraturan di MTsN 2 Sumedang - Naufal Ridotul Irfan; Enoh Nuroni; Dewi Mulyani (Bandung Conference Series: Islamic Education, 2023)
Abstract. Discipline is an attitude and behavior that reflects obedience to rules, regulations, and norms that apply both written and unwritten. With discipline, it is hoped that students will discipline themselves in obeying school rules so that the teaching and learning process runs smoothly and facilitates the goals of achieving education. Discipline functions in supporting the process of educational activities so that it runs smoothly and influences the creation of schools as an educational environment that is conducive to learning activities. Discipline can also have an impact on the growth of a good personality. Disciplined attitudes and behavior are formed through practice. Likewise, an orderly, orderly and obedient personality needs to be trained and accustomed to. The formation of a disciplined personality requires guidance from the teacher, this is done so that students can apply disciplinary behavior in their daily lives on the basis of their own desires without any coercion from parents or teachers. This study aims to determine the efforts of Akidah Akhlak teachers in fostering student discipline in implementing school rules in class VIII students. This type of research is descriptive qualitative field, which takes place at MTsN 2 Sumedang. The data sources used are primary and secondary data sources. Methods of data collection using three methods, namely the method of interviews (interview), observation (observation), and documentation then analyzed by means of inductive thinking. The data validation technique uses triangulation. Data analysis techniques namely reduction, data presentation and conclusion. Based on the description of the data from the survey results, the role of the Akidah Akhlak teacher in fostering student discipline in implementing school rules for class VIII students at MTsN 2 Sumedang is that the teacher has a role as an educator, namely the teacher conducts coaching, as a motivator, namely the teacher motivates students to be able to behave in discipline, as class manager and supervisor. As for the efforts that have been made by the teacher are by exemplary efforts, conducting supervision, providing motivation, giving punishment and sanctions to students who are not disciplined in conducting coaching there are supporting factors and inhibiting factors. The supporting factors are facilities and infrastructure, cooperation between school members, cooperation between the school and the surrounding community. The inhibiting factors are infrastructure, lack of teaching staff, lack of support from parents and the surrounding community. ABSTRAK. Kedisiplinan adalah suatu sikap dan prilaku yang mencerminkan ketaatan terhadap peraturan, tata tertib, serta norma-norma yang berlaku baik yang tertulis maupun tidak tertulis. Dengan adanya ketaatan diharapkan peserta didik mendisiplinkan diri dalam menaati peraturan sekolah sehingga proses belajar mengajar berjalan dengan lancar dan memudahkan tujuan pencapaian pendidikan. Ketaatan berfungsi dalam mendukung proses kegiatan pendidikan agar berjalan lancar dan memberi pengaruh bagi terciptanya sekolah sebagai lingkungan pendidikan yang kondusif bagi kegiatan pembelajaran. Sikap taat juga dapat memberi dampak bagi pertumbuhan kepribadian yang baik. Sikap dan prilaku taat terbentuk melalui latihan. Demikian pula kepribadian yang tertib, terarur dan patuh perlu dilatih dan dibiasakan. Pembentukan pribadi yang taat perlu adanya pembinaan dari guru hal ini dilakukan agar peserta didik dapat menerapkan prilaku taat dalam kehidupanya sehari-hari atas dasar keinginanya sendiri tanpa adanya perintah atau pemaksaan dari orang tua atau guru. Penelitian ini bertujuan untuk mendeskripsikan upaya guru Akidah Akhlak dalam meningkatkan ketaatan siswa terhadap peraturan sekolah pada siswa kelas VIII. Jenis penelitian ini adalah deskriptif kualitatif lapangan, yang mengambil lokasi di MTsN 2 Sumedang. Sumber data yang digunakan peneliti adalah sumber data primer dan skunder. Metode pengumpulan data menggunakan tiga metode diantaranya yaitu, metode wawancara (interview), observasi (pengamatan), dan dokumentasi kemudian dianalisis dengan cara berfikir induktif. Teknik analisa data yang digunakan yaitu Reduksi, Penyajian data dan Penarikan kesimpulan. Berdasarkan deskripsi data dari hasil pra survey adapun peranan guru Akidah Akhlak dalam meningkatkan ketaatan siswa terhadap peraturan sekolah pada siswa kelas VIII di MTsN 2 Sumedang adalah guru memiliki peranan sebagai edukator yaitu guru melakukan pembinaan ketaatan, sebagai motivator yaitu guru memotivasi siswa agar dapat berprilaku taat terhadap peraturan, sebagai pengelola kelas dan supervisor. adapun upaya yang telah dilakukan oleh guru aqidah akhlak adalah dengan upaya keteladanan, melakukan pengawasan, memberikan motivasi, memberikan hukuman dan sanksi pada siswa yang tidak taat terhadap peraturan dalam melakukan pembinaan terdapat faktor pendukung dan faktor penghambat. Faktor pendukung diantaranya adalah sarana dan prasarana, kerjasama antar warga sekolah, kerja sama antar pihak sekolah dengan masyarakat sekitar. Adapun faktor penghambatnya diantaranya yaitu sarana prasarana, kurangnya tenaga pengajar, kurangnya dukungan orangtua dan masyarakat sekitar.